The Characteristics of Farmers' Response to the Rice Reduction Policy on the Marshy Lowland in Southern Ibaraki Prefecture - TANO, Hiroshi (Annals of The Tohoku Geographycal Asocciation, 1985)
The rice reduction policy in Japan has been enforced since 1970 for the purpose of solving the problem of overproduction. This has largely influenced the paddy field land use throughout the country. Farmers' response to this policy varies by region. In this paper, the purpose of study is to consider both the factors making the variation among farmers' responses to this policy and the characteristics of one-crop farmers who have been influenced by the rice reduction policy. The areas of study are Miho and Azuma villages in Ibaraki Prefecture. The former is located in southern shore of Lake Kasumigaura and the latter in the lower plain of Tone river. These are typical one-crop areas, i. e., rice, in Kanto plain. Farmers have individually changed their crops in the Miho village. On the contrary, in the Azuma village, the crop changing is carried out by village community. The difference of these responses to the rice reduction policy largely depends upon the one of physical soil conditions and social conditions as follows: In the Miho village, soil of paddy field is drained or ill-drained. A lot of part-time farmers live in this region and they have farm fields under 1.5 ha. The main source of their income is not the farming income but full time salary in other industry. The influence of the rice reduction policy on household incomes is not so much as that of other one-crop paddy field regions. Consequently, individual farm household can allot other crops to their own drained paddy field at will. Moreover, these farmers get the same profit per 10 ares as that of rice growing by adopting both soybean growing which has a benefit of the crop changing subsidy, and wheat growing as a second crop. On the other hand, although most of the farmers are part-time employees in other industries in the Azuma village, their incomes mainly depend upon agricultural income and they can not expect so much other income. For this reason, they are much dependent on the paddy income. Most of the paddy field are consisted of ill-drained soil. Thus the farmer in this region took the passive attitude toward the early rice reduction policy. However, at the beginning of reinforcement of the rice reduction policy from 1978, a lot of farmers feared that the enforcement of this policy might diminish the farm house paddy income. In order to find a way out of these difficulties, it was proposed that the farmers should response to the rice reduction policy positively and change from one-crop farming to plural-crop farming to increase the income. For that reason, they carried out the land improvement and established the mutual cooperation system. Consequently, the crop changing area from paddy field exceeded double during the four years from 1978 to 1982. Mutual cooperation system means that the full-time farmers rent the crop changing area of paddy field from small part time farmers. As the result of the establishment of mutual cooperation system, the number of full-time farmers with plural-crop farming has increased. It clearly illustrates that mutual cooperation system played an important role in maintainnning and developing both full-time and part-time farming. However, the income of farmers with 2.0 ha farm has not increased after the establishment of the mutual cooperation system. Such problem will be an important subject for regional agriculture in the future.